SET-LRP of acrylates catalyzed by a 1 penny copper coin. Issue 43 (6th September 2016) - Aksakal, R.; Resmini, M.; Becer, C. R.
Abstract : Controlled polymerization of acrylates can be catalyzed by one of the cheapest catalysts, a 1 pence coin. Abstract : A British 1 penny coin (1 p) was used to polymerize a selection of hydrophobic and hydrophilic acrylate monomers using linear and star shaped initiators to obtain polymers even in 50 gram scale with low dispersity values ( Đ = 1.05–1.11). When compared with Cu wire systems, no induction period was observed, hence demonstrating an economic and easily accessible catalyst for SET-LRP acrylates.